Estudantes com deficiência no ensino superior brasileiro: uma análise censitária das matrículas nas instituições federais - Welder Rodrigo Vicente (2023)
This dissertation analyzed the enrollment of students with disabilities in federal institutions from 2010 to 2019, using microdata from the Higher Education census made available by Inep - Instituto Nacional de Ensino e Pesquisas Educacionais Anísio Teixeira. Academic productions published in Brazil after the implementation of the National Special Education Policy (PNE) were mapped, and the profile of students and the availability of accessibility resources in federal higher education institutions were analyzed and examined. In order to achieve the proposed objective, the dialectical approach was chosen, and as a methodological resource, for data collection for this dissertation, indicators were considered as an operational tool, from a pragmatic perspective. A descriptive study was carried out, taking the quantitative approach as its methodological matrix, identifying that the policies implemented in Brazil through the Include Program in 2005, the PNE in 2008, and 2016 with the quota law, contributed to the increase in the number of students with disabilities in Higher Education. After analyzing the data, it was identified that there was a slight increase in the enrollment of students with disabilities in Higher Education, with the predominant gender of students being male; as for race, mixed race stood out, and the predominant disability was physical disability, followed by low vision. It was also possible to see an increase in enrollment of students over 25 years of age. The data presented in this research qualify as propositions for future studies related to the area of Special Education.